Calcium Dobesilate (CaD) Attenuates High Glucose and High Lipid-Induced Impairment of Sarcoplasmic Reticulum Calcium Handling in Cardiomyocytes - Deng, Jianxin; Cai, Xiangsheng; Hao, Mingyu; Liu, Xueting; Chen, Zelong; Li, Haiyan; Liu, Junying; Liao, Yunxiu; Fu, Hao; Chen, Huiyan; Qin, Gangjian; Yan, Dewen (Frontiers in Cardiovascular Medicine, 2021)
Calcium dobesilate (CaD) is used effectively in patients with diabetic microvascular disorder, retinopathy, and nephropathy. Here we sought to determine whether it has an effect on cardiomyocytes calcium mishandling that is characteristic of diabetic cardiomyopathy. Cardiomyocytes were sterile isolated and cultured from 1-3 days neonatal rats and treated with vehicle (Control), 25mM glucose+300 M Palmitic acid (HG+PA), 100µM CaD (CaD), or HG+PA+CaD to test the effects on calcium signaling (Ca2+ sparks, transients, and SR loads) and reactive oxygen species (ROS) production by confocal imaging. Compared to Control, HG+PA treatment significantly reduced field stimulation-induced calcium transient amplitudes (2.22±0.19 vs 3.56±0.21, p<0.01) and the levels of caffeine-induced calcium transients (3.19±0.14 vs. 3.72±0.15, p<0.01), however significantly increased spontaneous Ca2+ sparks firing levels in single cardiomyocytes (spontaneous frequency 2.65±0.23 vs. 1.72±0.12, p<0.01) and ROS production (67.12±4.4 vs. 47.65±2.12, p<0.05), which suggest that HG+PA treatment increases Ca2+ spark-mediated SR Ca2+ leak, causing partial depletion of SR Ca2+ content and consequently decreased systolic Ca2+ transient. Remarkably, these impairments in calcium signaling and ROS production were largely prevented by pre-treatment of the cells with CaD. Therefore, CaD may contribute to a good protective effect on patients with calcium mishandling and contractile dysfunction in cardiomyocytes associated with diabetic cardiomyopathy.